Peran Guru dalam Pembelajaran Abad 21 di SDN 1 Mansalean Kabupaten Banggai Laut - Rizkiani, Rizkiani; Halidu, Salma; Sarlin, Muhammad (Ideas Publishing, 2024)
Learning is a learning process built by teachers to improve moral, intellectual, and develop various abilities possessed by students, including thinking abilities, creative abilities, knowledge construction abilities, problem solving abilities, and the ability to master learning material well. The aim to be achieved in this research is to describe the role of teachers in 21st century learning at SDN 1 Mansalean, Banggai Laut Regency. This type of research uses qualitative research. The teacher has tried to carry out his role as a teacher in implementing 21st century learning at SDN 1 Mansalean by using various learning models and methods to encourage students to be more active in learning